Anti tumor necrosis factor induced focal myositis. (17th December 2022) - Masnammany, Adrian Mark; Lau, Wendy; Wong, Peter Kee Kee; Manolios, Nicholas
Tumour necrosis factor inhibitors (TNFis) can trigger autoantibody formation and, in a small proportion of patients, result in symptomatic autoimmune diseases, including polymyositis and dermatomyositis. Focal myositis presents with localized muscle pain and is diagnosed based on magnetic resonance imaging (MRI), electromyography (EMG) and muscle histopathology. We report the first case of TNFi-induced focal myositis in the left thigh of a patient with ulcerative colitis on infliximab. A 30-year-old lady presented with left thigh pain with no other systemic manifestation or muscle weakness. The immunology profile showed positivity of antinuclear antibody (ANA), high titre of anti-ds-DNA, and anti-Mi-2 without any features of systemic lupus erythematosus or dermatomyositis. Discontinuation of the TNFi and commencement of glucocorticoids resulted in the resolution of the myositis.